Is innovation the key to solving the productivity paradox? - Tomasz Kijek; Arkadiusz Kijek (Journal of Innovation & Knowledge (JIK), 2019)
The productivity paradox has sparked a great deal of research during the past three decades. Unfortunately, neither the results of empirical research nor the theoretical explanations for the paradox provide a convincing answer to whether investments in information and communication technology (ICT) affect the productivity of firms, sectors, and economies. This study aims to solve the productivity paradox by analysing the moderating effect of technological innovations on the link between ICT and productivity. The sample covers 2960 Polish innovative manufacturing firms. The research uses Generalized Structural Equation Model (GSEM). The findings clarify the productivity paradox and show that process innovations exert a moderating effect on the link between ICT and labour productivity in the sample firms.
Keywords: C3; D8; D9; O3; 650; Productivity paradox; ICT; Innovation; Knowledge production function; GSEM